Dynamic Model of Markets of Successive Product Generations - Joachim Kaldasch (British Journal of Economics, Management & Trade, 2015)
A dynamic microeconomic model is presented that establishes the price and unit sales evolution of heterogeneous goods consisting of successive homogenous product generations. It suggests that for a fast growing supply the mean price of the generations are governed by a logistic decline towards a floor price. It is shown that generations of a heterogeneous good are in mutual competition. Their market shares are therefore governed by a Fisher-Pry law while the total unit sales are governed by the lifecycle dynamics of the good. As a result the absolute unit sales of a generation exhibit a characteristic sales peak consisting of a rapid increase followed by a long tail. The presented approach shows that the evolution of successive product generations can be understood as an evolutionary adaptation process. The applicability of the model is confirmed by a comparison with empirical investigations on successive DRAM generations.
Additional information: Article no. BJEMT.20473
Keywords: C0; C1; D0; D11; L11; 330; Product diffusion; multiple generations; evolutionary economics; competition; price evolution; DRAM market